Skeletal muscle alkaline Pi pool is decreased in overweight-to-obese sedentary subjects and relates to mitochondrial capacity and phosphodiester content. - Valkovič, L; Chmelík, M; Ukropcová, B; Heckmann, T; Bogner, W; Frollo, I; Tschan, H; Krebs, M; Bachl, N; Ukropec, J; Trattnig, S; Krššák, M (Nature Publishing Group, 2016)
Defects in skeletal muscle energy metabolism are indicative of systemic disorders such as obesity or type 2 diabetes. Phosphorus magnetic resonance spectroscopy ((31)P-MRS), in particularly dynamic (31)P-MRS, provides a powerful tool for the non-invasive investigation of muscular oxidative metabolism. The increase in spectral and temporal resolution of (31)P-MRS at ultra high fields (i.e., 7T) uncovers new potential for previously implemented techniques, e.g., saturation transfer (ST) or highly resolved static spectra. In this study, we aimed to investigate the differences in muscle metabolism between overweight-to-obese sedentary (Ob/Sed) and lean active (L/Ac) individuals through dynamic, static, and ST (31)P-MRS at 7T. In addition, as the dynamic (31)P-MRS requires a complex setup and patient exercise, our aim was to identify an alternative technique that might provide a biomarker of oxidative metabolism. The Ob/Sed group exhibited lower mitochondrial capacity, and, in addition, static (31)P-MRS also revealed differences in the Pi-to-ATP exchange flux, the alkaline Pi-pool, and glycero-phosphocholine concentrations between the groups. In addition to these differences, we have identified correlations between dynamically measured oxidative flux and static concentrations of the alkaline Pi-pool and glycero-phosphocholine, suggesting the possibility of using high spectral resolution (31)P-MRS data, acquired at rest, as a marker of oxidative metabolism.